PERMAINAN TRADISIONAL GICI-GICI DALAM PENGEMBANGAN KETERAMPILAN MOTORIK KASAR MURID KELAS IV SEKOLAH DASAR - Luis Rumparmpam (Journal of Education Papua Baru, 2026)
Abstract: This study synthesizes a thesis-based discussion of the traditional game Gici-Gici as a culturally responsive medium for developing gross motor skills among fourth-grade elementary school students. It responds to the decline of children’s active play, limited physical education facilities, and the need to integrate Papuan local wisdom into elementary learning. Using a qualitative literature review and theoretical synthesis, the study examines motor development, physical education, traditional games, ethno-pedagogy, character education, and school management. The synthesis shows that Gici-Gici integrates locomotor, non-locomotor, and manipulative movements, such as single-leg hopping, jumping, landing, balancing, bending, turning, and throwing a marker. These movements support balance, lower-limb strength, postural control, coordination, and movement confidence. The game also strengthens affective and social learning through rules, turn-taking, honesty, cooperation, responsibility, and sportsmanship. The study concludes that revitalizing Gici-Gici is both cultural preservation and an instructional strategy for motor development, character education, local curriculum innovation, and school resource optimization. Keywords: traditional game; Gici-Gici; gross motor skills; ethno-pedagogy; elementary school   Abstrak: Penelitian ini menyintesis kajian berbasis tesis tentang permainan tradisional Gici-Gici sebagai media budaya untuk mengembangkan keterampilan motorik kasar murid kelas IV sekolah dasar. Kajian ini dilatarbelakangi oleh menurunnya aktivitas bermain aktif anak, keterbatasan sarana pendidikan jasmani, dan kebutuhan mengintegrasikan kearifan lokal Papua ke dalam pembelajaran. Dengan pendekatan kualitatif melalui telaah pustaka dan sintesis teoretis, penelitian ini menelaah perkembangan motorik, pendidikan jasmani, permainan tradisional, etnopedagogi, pendidikan karakter, dan manajemen sekolah. Hasil sintesis menunjukkan bahwa Gici-Gici memuat gerak lokomotor, nonlokomotor, dan manipulatif, seperti melompat satu kaki, meloncat, mendarat, menjaga keseimbangan, membungkuk, berputar, dan melempar gacu. Gerak tersebut mendukung keseimbangan, kekuatan tungkai bawah, kontrol postural, koordinasi, dan keberanian bergerak. Permainan ini juga menguatkan pembelajaran afektif dan sosial melalui aturan bermain, menunggu giliran, kejujuran, kerja sama, tanggung jawab, dan sportivitas. Penelitian ini menegaskan bahwa revitalisasi Gici-Gici merupakan pelestarian budaya sekaligus strategi instruksional untuk pengembangan motorik, pendidikan karakter, inovasi kurikulum lokal, dan optimalisasi sumber daya sekolah.. Kata kunci: permainan tradisional; Gici-Gici; motorik kasar; etnopedagogi; sekolah dasar